Understanding organizational commitment among scout volunteers within non-formal education - Yani Rahmawati,; Zainal Abiddin, Norhasni; Ro'is, Ihsan (Pusat Pengembangan dan Publikasi Karya Ilmiah (P3KI) Sekolah Pascasarjana Universitas Pendidikan Indonesia, 2015)
Organizational commitment considered as an important issue in any types of organization. Many studies have been addressed on organizational commitment among profit worker. Oppositely, studies about organizational commitment addressed for volunteer to run the program generally engage with non-profit organization tend to be lack. Therefore, this study was conducted to emerge organizational commitment in different aspect within non-profit organization especially relate to non-formal element. As regards to the extension education, the objective of the study is to examine relationship between satisfaction and organizational commitment among scout volunteer. The research used quantitative method to analyze the data. The instrument was used self administered questionnaire adapted from previous studies. It was divided into several parts: demographic, Volunteer Satisfaction Index (VSI) and Organizational commitment (OCQ). The questionnaire was administered to 220 respondents from scout center organization in Samarinda-East Kalimantan, Indonesia. The sample was taken using sample random technique. The data was analyzed both descriptive as well as inferential statistic. The finding of the study revealed that two of four dimensions from job satisfaction namely support and group integration considered having correlation towards organizational commitment, conversely, organizational efficacy and empowerment were failed to have correlation with organizational commitment. Several implications and recommendation related with the subject were provided relate with this study.